Implementation of Public-Private Partnership in Housing Programme and Affordable Housing in the Federal Capital Territory, Nigeria - Sule, Kabiru; Esidene , Erunke Canice; Adadu, Yahaya Abdullahi (Kashere Journal of Politics and International Relations, 2023)
Despite multiple schemes implemented by various governments around the country, affordable housing remains elusive to the average Nigerian. Because the situation is comparable to that of other developing nations, it remains a key concern in these countries socioeconomic development. Over 52% of Nigeria’s population has been claimed to live in shanties, squatter communities and informal settlements. This study, therefore, examined Implementation of Public-Private Partnership in Housing Programme and Affordable Housing in the Federal Capital Territory (FCT), Nigeria. The study adopted survey research design. The primary source includes data gathered from distribution of questionnaires to Federal Capital Development Authority (FCDA). A sample size of three hundred and eighty five (385) was selected for the study. The study found among other things that the implementation of Public-Private Partnership (PPP) in housing programme and affordable housing in the Federal Capital Territory (FCT), Nigeria, has shown promising results in addressing the challenges of affordable housing but hasn’t actually been able to ensure that all citizens/residents have access to decent housing accommodation at affordable cost as rightly enshrined in the National Housing Policy goal and objective. The study therefore recommended among other things that Federal Capital Territory Administration (FCTA) should enhance and streamline the legal and regulatory framework governing PPPs in the housing sector.